Hibernacula of greater horseshoe bat Rhinolophus ferrumequinum (Schreber, 1774): data from four deep caves in Slovenia - Aja Zamolo; Teo Delić (Natura Sloveniae)
In this paper, we present data on not yet surveyed hibernacula of the greater horseshoe bat (Rhinolophus ferrumequinum) from three deep caves in SE Slovenia (Čaganka, Kaščica, Topli vrh 5) and one in W Slovenia. We found between 161 and 255 overwintering greater horseshoe bats in the caves, in addition to six other species. These data show that some deep caves are still unexplored for bats, although bat sightings have been reported in the past. Targeted survey of caves that are harder to access or those from which larger number of bats have been reported from could contribute not only additional distribution data, but also data on higher concentrations of hibernating bats.